2003
DOI: 10.1104/pp.103.020016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci and Comparative Genomics of Cereal Cell Wall Composition

Abstract: Quantitative trait loci (QTLs) affecting sugar composition of the cell walls of maize (Zea mays) pericarp were mapped as an approach to the identification of genes involved in cereal wall biosynthesis. Mapping was performed using the IBM (B73 × Mo17) recombinant inbred line population. There were statistically significant differences between B73 and Mo17 in content of xylose (Xyl), arabinose (Ara), galactose (Gal), and glucose. Thirteen QTLs were found, affecting the content of Xyl (two QTLs), Ara (two QTLs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 58 publications
5
60
0
Order By: Relevance
“…The IBM population also has a relatively large population size, with $300 lines being available. The authors are aware of only one published mapping study using the full IBM population (Hazen et al 2003), in which QTL for cell wall composition were mapped to intervals spanning $10 cM. Another published study used 94 lines of the IBM population to map QTL controlling the thermal properties of maize starch (Scott and Duvick 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IBM population also has a relatively large population size, with $300 lines being available. The authors are aware of only one published mapping study using the full IBM population (Hazen et al 2003), in which QTL for cell wall composition were mapped to intervals spanning $10 cM. Another published study used 94 lines of the IBM population to map QTL controlling the thermal properties of maize starch (Scott and Duvick 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the major significant difference between this previous study and the study reported here, apart from the years in which they were conducted, was that, in the present study, an independently derived B73 3 Mo17 AIL population was employed. AIL populations have been used successfully in animals and plants to localize QTL to relatively narrow chromosomal segments (e.g., Hazen et al 2003;Wang et al 2003). Studies in mice found greater precision of QTL detection in an F 11 AIL population compared to an F 2 population (Iraqi et al 2000;Hernandez-Valladares et al 2004).…”
Section: Mo17 Advanced Intercross Recombinant Inbred Line Population mentioning
confidence: 99%
“…Mapping experiments using AILs in animals and plants have been published (Iraqi et al 2000;Hazen et al 2003;Wang et al 2003;Jagodic et al 2004;Hernandez-Valladares et al 2004;Scott and Duvick 2005;Yu et al 2007;Balint-Kurti et al 2007Rodriguez et al 2008;Capelle et al 2010). In maize, the IBM population (for Intermated B73 3 Mo17, Lee et al 2002), is widely used by the maize international community for high-density genetic mapping Fu et al 2006) and fine mapping of traits of interest (Hazen et al 2003;Scott and Duvick 2005;Balint-Kurti et al 2007Rodriguez et al 2008).…”
Section: Q Uantitative Trait Loci (Qtl) Mapping Providesmentioning
confidence: 99%
“…In maize, the IBM population (for Intermated B73 3 Mo17, Lee et al 2002), is widely used by the maize international community for high-density genetic mapping Fu et al 2006) and fine mapping of traits of interest (Hazen et al 2003;Scott and Duvick 2005;Balint-Kurti et al 2007Rodriguez et al 2008). Balint-Kurti et al (2007 were the first to compare the precision of QTL detection in conventional recombinant inbred lines (RILs) and intermated RILs, derived from the same parental lines, for two disease resistance traits in maize.…”
Section: Q Uantitative Trait Loci (Qtl) Mapping Providesmentioning
confidence: 99%
“…Whereas cellulose is chemically homogeneous and available in highly pure forms, hemicelluloses are more diverse, both between plant species and between tissues within a single plant. Dicotyledonous hemicelluloses, for example, contain fucose, O-acetylated galactose, and α1,6-xylose-substituted β1,4-glucan [10,19,46]. Enzymes that are necessary to degrade the linkages found in dicot hemicelluloses therefore include β1,4-glucanases (which can be specialized for hemicelluloses such as xyloglucan), α-fucosidase, α-glucuronidase, β1,4-xylanase, α-and β-xylosidase, α-arabinosidase, and several classes of esterase.…”
Section: Enzymes For Biomass Conversionmentioning
confidence: 99%